Moral Expertise New Essays from Theoretical and Clinical Bioethics (Philosophy and Medicine, 2018)
This collection addresses whether ethicists, like authorities in other fields, can speak as experts in their subject matter. Though ethics consultation is a growing practice in medical contexts, there remain difficult questions about the role of ethicists in professional decision-making. Contributors examine the nature and plausibility of moral expertise, the relationship between character and expertise, the nature and limits of moral authority, how one might become a moral expert, and the trustworthiness of moral testimony. This volume engages with the growing literature in these debates and offers new perspectives from both academics and practitioners. The readings will be of particular interest to bioethicists, clinicians, ethics committees, and students of social epistemology. These new essays promise to advance discussions in the professionalization and accreditation of ethics consultation.